IMPLIKASI KUNJUNGAN WISATAWAN GAY DI SEMINYAK, BALI - Prabawati, Ni Putu Diah; Kumbara, Anak Agung Ngurah Anom; Pujaastawa, Ida Bagus Gde (Jurnal Master Pariwisata (JUMPA), 2019)
Gay tourist visits are a paradoxical phenomenon when viewed from the concept of Balinese cultural tourism. However, gay tourists exist in the Seminyak, Bali area. The purpose of this study is to examine the socio-economic, cultural, health implications of gay tourist visits and the  responses of local community in Seminyak. The research method used was semi-structured interviews with 20 informants. The results of this study are that gay tourist visits have a positive effect on employment and community income. The culture of society is not affected, on the contrary the community is more proactive in preserving culture. No physical and non-physical health implications were found in the community. The level of response of the some Seminyak community to  gay tourist visits has become apathy, and the annoyance shown by people who feel disturbed by gay tourists. The reseachers hope that this finding is going to be take into consideration for the development of tourism in Seminyak. Keywords : gay tourists, tourism implications, people's responses, Seminyak